The pathomorphological characteristics of clear-cell adenocarcinomas of the ovary and its mixed tumors with a clear-cell component - M.. D Akhmedova; M. A. Shabanov; V. V. Barinov; K. I. Zhordania; L. I. Bokina; E. A. Mustafina (Опухоли женской репродуктивной системы, 2014)
Objective: to study the pathomorphological signs of pure and mixed clear-cell ovarian tumors with a clear-cell component.Subjects and methods. The clinical and morphological characteristics and the course of the disease were analyzed in 96 patients aged 21 to 75 years with clear-cell ovarian carcinoma. All the patients were divided into 2 groups: 1) 71 patients with pure clear-cell ovarian adenocarcinomas (COA) and 2) 25 patients with mixed malignant ovarian epithelial tumors (MMOET) with an obligatory clear-cell component. All pure forms of ovarian clear-cell malignancies were represented by adenocarcinoma in our study. This histologic type of the tumor was also prevalent among mixed ovarian neoplasms.Results. Clear, optically transparent cells and shoe nail-type (nail) ones were most common in COA. MMOETs showed moderate dif- ferentiation and malignancy and moderate atypia of a cell. Pure clear-cell neoplasms generally displayed 3 to 6 mitoses in 10 fields of vision whereas MMOET exhibited as many as 3 mitoses in 10 fields of vision.